Effectiveness of Zinc Supplementation in Nutritional Catch-Up Growth Management for Stunted Toddlers: A Systematic Review of Randomized Controlled Trials and Primary Studies - Kartika Dewi (The International Journal of Medical Science and Health Research, 2026)
Introduction: Stunting affects 148.1 million children under five globally, with zinc deficiency mechanistically implicated through impaired IGF-1 signaling and cellular proliferation. This systematic review evaluates the effectiveness of zinc supplementation on linear growth, ponderal growth, biomarkers, and morbidity outcomes in stunted toddlers. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines from inception to June 2025. Included studies comprised RCTs, cluster-RCTs, or primary studies enrolling children aged 0–72 months receiving oral zinc supplementation with at least one anthropometric or morbidity outcome. Risk of bias was assessed using Cochrane RoB 2.0. Narrative synthesis was employed with pooled estimates derived from included meta-analyses. Results:  Zinc supplementation significantly improved linear growth in stunted children (effect size 0.13–0.50 SD), with the most pronounced effect in Ethiopian infants (7.0 cm vs 2.8 cm placebo, p<0.001). Weight gain showed consistent positive effects (ES 0.309, 95% CI 0.178–0.439). Serum zinc responded robustly (ES 0.820). Zinc reduced diarrhea (OR 0.82, 95% CI 0.72–0.93) and pneumonia (OR 0.59, 0.41–0.83). All-cause mortality was reduced by 16% (SRR 0.84). However, stunting prevalence was not consistently reduced, with attenuation observed in settings with high environmental enteric dysfunction or iron co-supplementation. Discussion: Zinc demonstrates significant benefit for linear growth velocity in zinc-deficient stunted toddlers, mediated through IGF-1 upregulation, improved appetite, and reduced infectious morbidity. Contextual heterogeneity is driven by baseline zinc status, co-existing deficiencies, EED burden, and iron co-supplementation. Conclusion: Zinc supplementation at 10 mg/day for ≥24 weeks is effective for improving linear growth velocity and reducing morbidity in stunted toddlers with zinc deficiency, though insufficient as monotherapy for reversing stunting prevalence. Integrated approaches addressing multifactorial etiology are recommended.